Efficient nonparametric identification for high-precision motion systems: A practical comparison based on a medical X-ray system. (November 2016) - van der Maas, Rick; van der Maas, Annemiek; Dries, Johan; de Jager, Bram
Abstract: The need for accurate knowledge of complex dynamical behavior for high-performance mechatronic systems led to the development of a vast amount of nonparametric system identification approaches over the recent years. The aim of this paper is to compare several proposed methods based on experiments on a physical complex mechanical system to bridge the gap between identification theory and practical applications in industry where basic identification approaches are often the norm. Typical practical implications such as operation under closed-loop control, multivariable coupled behavior and nonlinear effects are included in the analysis. Finally, a possible approach for fast and reliable identification is illustrated based on measurement results of an interventional medical X-ray system.